Difference between revisions of "009B Sample Final 1, Problem 7"
Jump to navigation
Jump to search
Line 1: | Line 1: | ||
::<span class="exam">a) Find the length of the curve | ::<span class="exam">a) Find the length of the curve | ||
− | ::::::<math>y=\ln (\cos x),~~~0\leq x \leq \frac{\pi}{3}</math> | + | ::::::<math>y=\ln (\cos x),~~~0\leq x \leq \frac{\pi}{3}.</math> |
::<span class="exam">b) The curve | ::<span class="exam">b) The curve | ||
Line 14: | Line 14: | ||
|Recall: | |Recall: | ||
|- | |- | ||
− | |'''1.''' The formula for the length <math style="vertical-align: 0px">L</math> of a curve <math style="vertical-align: -5px">y=f(x)</math> where <math style="vertical-align: -3px">a\leq x \leq b</math> is | + | | |
+ | ::'''1.''' The formula for the length <math style="vertical-align: 0px">L</math> of a curve <math style="vertical-align: -5px">y=f(x)</math> where <math style="vertical-align: -3px">a\leq x \leq b</math> is | ||
|- | |- | ||
| | | | ||
− | ::<math>L=\int_a^b \sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math> | + | :::<math>L=\int_a^b \sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math> |
|- | |- | ||
− | |'''2.''' <math style="vertical-align: -14px">\int \sec x~dx=\ln|\sec(x)+\tan(x)|+C.</math> | + | | |
+ | ::'''2.''' <math style="vertical-align: -14px">\int \sec x~dx=\ln|\sec(x)+\tan(x)|+C.</math> | ||
|- | |- | ||
− | |'''3.''' The surface area <math style="vertical-align: 0px">S</math> of a function <math style="vertical-align: -5px">y=f(x)</math> rotated about the <math style="vertical-align: -4px">y</math>-axis is given by | + | | |
+ | ::'''3.''' The surface area <math style="vertical-align: 0px">S</math> of a function <math style="vertical-align: -5px">y=f(x)</math> rotated about the <math style="vertical-align: -4px">y</math>-axis is given by | ||
|- | |- | ||
| | | | ||
− | ::<math style="vertical-align: -13px">S=\int 2\pi x\,ds</math>, where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}.</math> | + | :::<math style="vertical-align: -13px">S=\int 2\pi x\,ds</math>, where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}.</math> |
|} | |} | ||
Line 36: | Line 39: | ||
|First, we calculate  <math>\frac{dy}{dx}.</math> | |First, we calculate  <math>\frac{dy}{dx}.</math> | ||
|- | |- | ||
− | |Since <math style="vertical-align: - | + | |Since <math style="vertical-align: -5px">y=\ln (\cos x),</math> |
+ | |- | ||
+ | | | ||
+ | ::<math>\frac{dy}{dx}=\frac{1}{\cos x}(-\sin x)=-\tan x.</math> | ||
|- | |- | ||
|Using the formula given in the Foundations section, we have | |Using the formula given in the Foundations section, we have | ||
|- | |- | ||
| | | | ||
− | ::<math>L=\int_0^{\pi/3} \sqrt{1+(-\tan x)^2}~dx</math> | + | ::<math>L=\int_0^{\pi/3} \sqrt{1+(-\tan x)^2}~dx.</math> |
|} | |} | ||
Line 76: | Line 82: | ||
& = & \displaystyle{\ln (2+\sqrt{3})}. | & = & \displaystyle{\ln (2+\sqrt{3})}. | ||
\end{array}</math> | \end{array}</math> | ||
− | |||
− | |||
|} | |} | ||
Line 85: | Line 89: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We start by calculating  <math>\frac{dy}{dx}</math> | + | |We start by calculating  <math>\frac{dy}{dx}.</math> |
|- | |- | ||
− | |Since <math style="vertical-align: -13px">y=1-x^2,~ \frac{dy}{dx}=-2x</math> | + | |Since <math style="vertical-align: -13px">y=1-x^2,~ \frac{dy}{dx}=-2x.</math> |
|- | |- | ||
|Using the formula given in the Foundations section, we have | |Using the formula given in the Foundations section, we have | ||
Line 100: | Line 104: | ||
|Now, we have <math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math> | |Now, we have <math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math> | ||
|- | |- | ||
− | |We proceed by using trig substitution. Let <math style="vertical-align: -13px">x=\frac{1}{2}\tan \theta</math> | + | |We proceed by using trig substitution. Let <math style="vertical-align: -13px">x=\frac{1}{2}\tan \theta.</math> Then, <math style="vertical-align: -12px">dx=\frac{1}{2}\sec^2\theta \,d\theta.</math> |
|- | |- | ||
|So, we have | |So, we have | ||
Line 115: | Line 119: | ||
!Step 3: | !Step 3: | ||
|- | |- | ||
− | |Now, we use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=\sec \theta</math> | + | |Now, we use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=\sec \theta.</math> Then, <math style="vertical-align: -1px">du=\sec \theta \tan \theta \,d\theta.</math> |
|- | |- | ||
|So, the integral becomes | |So, the integral becomes |
Revision as of 12:24, 18 April 2016
- a) Find the length of the curve
- b) The curve
- is rotated about the -axis. Find the area of the resulting surface.
Foundations: |
---|
Recall: |
|
|
|
|
|
Solution:
(a)
Step 1: |
---|
First, we calculate |
Since |
|
Using the formula given in the Foundations section, we have |
|
Step 2: |
---|
Now, we have: |
|
Step 3: |
---|
Finally, |
|
(b)
Step 1: |
---|
We start by calculating |
Since |
Using the formula given in the Foundations section, we have |
|
Step 2: |
---|
Now, we have |
We proceed by using trig substitution. Let Then, |
So, we have |
|
Step 3: |
---|
Now, we use -substitution. Let Then, |
So, the integral becomes |
|
Step 4: |
---|
We started with a definite integral. So, using Step 2 and 3, we have |
|
Final Answer: |
---|
(a) |
(b) |